Isolation and characterization of LHY homolog gene expressed in flowering tissues of Tectona grandis (teak) - Basherudin, Norlia; Muhammad, Norwati; Adnan, Norwati; Haron, Mohd Rosli; Mohd Saleh, Norihan (Academic Journals, 2008)
Floral initiation of teak through molecular biology approach is being studied for better understanding of teak flower development. Through PCR subtractive hybridization method, LHY homolog gene has been isolated from teak flowering tissues. The full-length cDNA of the gene was 2948 base pair (bp) and potentially encoded for 768 amino acids. It was named Tectona grandis LHY (Tg-LHY), as the gene was similar to the LHY gene of some species. Amino acid sequence alignment revealed that Tg-LHY was similar to LHY of Castanea sativa, LHY ofPhaseolus vulgaris and LHY of Arabidopsis thaliana. The highly conserved region found in Tg-LHY was the MYB protein, which is the DNA-binding protein responsible in negative feedback loop reaction of central oscillator in plant circadian clock system. The level of gene expression was found to be high four hours after dawn in flowering shoots and flower. This paper reported the isolation and characterization of the gene.